Oil Price Shocks and Economic Growth in Oil Exporting Countries: A Case Study of a Small Open Economy - Fadare, Samuel O.; Oladipo, Olajide; Agama, Emomotimi (International Journal of Energy Economics and Policy, 2025)
This study investigates the relationship between oil price shocks and economic growth in a small open economy which is also a prominent oil-exporting economy. The research employs annual time series data from 1996 to 2022 and error correction method (ECM) to analyze the impact of variations in oil prices on Nigeria’s economic performance. The study unraveled the nuanced mechanisms driving the interaction between oil price volatility and economic performance in our case, small open economy, Nigeria. In addition, the research explores the mechanisms through which oil price shocks transmit to the broader economy, considering factors such as government policies, institutional frameworks, and the structure of Nigeria’s oil-dependent economy. Findings revealed that in the short-run as well as long-run, oil price volatilities, investments, and oil revenues have a negative effect on economic growth. Indeed investments, whether lagged by 1-year or not lagged at all, has a negative effect on economic growth in Nigeria. The study will equip policymakers and other stakeholders’ valuable knowledge to formulate more robust policies aimed at mitigating the adverse impacts of oil price volatility on Nigeria’s economic growth prospects and foster sustainable economic development strategy in Nigeria.